Paramount 1000 Words In Pictures : Yellow - Zain ,Shama (Karachi PARAMOUNT BOOKS (PVT) LTD.)
PARAMOUNT 1000 WORDS SERIES IS A COLLECTION OF THREE DELIGHTFUL BOOKS DESIGNED FOR YOUNG AND CURIOUS MINDS. THE BASIC PURPOSE OF DEVELOPING THIS SERIES IS TO HELP KIDS DISCOVER THE WORLD.